Republic of Slovenia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper examines the progress of Slovenia by focusing on four interrelated topics that are critically important to the evolution of the transition process and provides insights into the work that lies ahead. The paper concludes that the voucher-based privatization process has failed to truly transform the ownership structure of socially owned enterprises. The paper also investigates the inflation process in Slovenia through an empirical examination of some commonly used determinants of inflation in transition economies.